RELATIONSHIP BETWEEN PSYCHOEMOTIONAL DISORDERS WITH INCREASING THICKNESS OF INTIMA-MEDIA COMPLEX AND VASCULAR MICRO INFLAMMATION DEVELOPMENT - A. P. Shavrin; B. V. Golovskoy (Klinicist)
Objective — to study relationship of psycho-emotional factors and indicators of intravascular microinflammation and vascular changes in healthy patients.Materials and methods. To study psycho-emotional status in 239 healthy patients aged 30 to 60 years, markers of inflammation (C-reactiveprotein — CRP and cytokines — tumor necrosis factor-α — TNF-α, interleukins — IL-1, -4, - 8) and ultrasonography of the vascular wall of the common carotid artery with the definition of the thickness of intimamedia.Results. In group with high levels of emotional stress significant increase in the thickness of intima media and increase in plasma concentrationsof markers of vascular mikrovospaleniya — CRP, IL-1, IL-8, TNF-α were showed. These correlation analysis indicated relationship between thickness of intima-media, psychoemotional factors and markers of vascular microinflamation. Calculating odds ratios revealed that thickening of the intima-media process such psycho-emotional disorders like anxiety, depression and fatigue are of great importance.Conclusion. Otherwise development of latent intravascular inflammation and thickening intima-media complex of common carotid artery is registered inhealthy patients with presence of psycho-emotional disorders (depression, anxiety, fatigue).